(untitled) (Nexo Revista Científica, 2023)
The purpose of this study is to investigate the effect of resilience for the selection as well as ranking suppliers with Fuzzy DEMATEL (Case study: Tabriz Compressor Manufacturing Company). The industrial engineers and production planners of Company were included in this study. For information gathering the questionnaire designed by the researchers was used. The Fuzzy DEMATEL method has been used to investigate the factors affecting resilience in the selection of suppliers. Also, Fuzzy VIKOR and COPRAS-G method has been used to compare and to represent ranking suppliers. Since COPRAS-G approach is used to analyze the different alternatives, and to estimate the alternatives based on their significance, degree of utility and the decision makers’ support to make more accurate decisions. In this regard, thirteen criteria have been selected by industrial experts. Based on the results obtained from Fuzzy DEMATEL, cost, quality, delivery time, and risk factor are ranked respectively. Additionally, after comparing Fuzzy Vikor and COPPRAS-G, the results obtained from COPRAS-G showed the best ranked amounts throughout different alternatives. Finally, the results obtained from COPRAS-G showed the traditional criteria in resilience supplier selection ranked the first and supplier selection from the stakeholders’ perspectives placed in second order. Furthermore, utility values and ranking candidate alternatives showed that the green supplier (A5) ranked the first, selection of suppliers (A3) was the next, following the traditional criteria (A1), supplier criteria(A4), supplier selection from the stakeholders’ perspectives (A2), as the remaining ranks, respectively.